Efficacy of pyrethroid-neonicotinoid mixture formulations against different developmental stages of tropical bed bug (Hemiptera: Cimicidae) - Von, Kok Yean; Lim, Li; Abdul Hafiz Ab Majid (Penerbit Universiti Kebangsaan Malaysia, 2024)
Bed bugs are urban pests as they are closely associated with humans to obtain blood meals. Many insecticides have been used against them, rendering them resistant to most of the insecticide formulations. Thus, novel insecticide formulations are in high demand. This study aimed to evaluate the efficacy of pyrethroid-neonicotinoid mixture formulations against Cimex hemipterus. The Penang Island-strain C. hemipterus was collected and subjected to residual insecticide bioassay and egg immersion treatment. The analysis of the knockdown and lethal time values imposed on 50% and 95% populations (10-d KT50, 10-d KT95, 10-d LT50, and 10- d LT95) revealed the orders of relative contact toxicity for all developmental stages (except eggs) of C. hemipterus as follows: porous surface – bifenthrin and imidacloprid > lambdacyhalothrin > alpha-cypermethrin and dinotefuran; non-porous surface – alpha-cypermethrin and dinotefuran > bifenthrin and imidacloprid > lambda-cyhalothrin. The hatching rates of C. hemipterus eggs remained high (84.17 – 100.00%) after being immersed in the tested insecticides, except alpha-cypermethrin and dinotefuran diluted at 50000 ppm. Thus, the overall performance of novel pyrethroid-neonicotinoid insecticide mixture formulations was mediocre.